Ghrelin Inhibits Proinflammatory Responses and Prevents Cognitive Impairment in Septic Rats. Issue 5 (May 2015) - Wei, Hua; Cao, Xiaohua; Zeng, Qingwen; Zhang, Fujun; Xue, Qingsheng; Luo, Yan; Lee, Jae-Woo; Yu, Buwei; Feng, Xiaomei
<x xml:space="preserve">Abstract</x> Objectives: A novel stomach-derived peptide, ghrelin, is down-regulated in sepsis and its IV administration decreases proinflammatory cytokines and mitigates organ injury. In this study, we wanted to investigate the effects of ghrelin on proinflammatory responses and cognitive impairment in septic rats. Design: Prospective, randomized, controlled experiment. Setting: Animal basic science laboratory. Subjects: Sprague-Dawley rats, weighing 250–300 g. Interventions: Sepsis was induced by cecal ligation and puncture. Animals were randomly divided into four groups: sham, sham + ghrelin, cecal ligation and puncture, and cecal ligation and puncture + ghrelin. Saline was given subcutaneously (30 mL/kg) at 4 and 16 hours after surgery for all rats. Septic rats were treated with ceftriaxone (30 mg/kg) and clindamycin (25 mg/kg) subcutaneously at 4 and 16 hours after surgery. Ghrelin (80 μg/kg) was administrated intraperitoneally 4 and 16 hours after surgery in sham + ghrelin group and cecal ligation and puncture + ghrelin group. Measurements and Main Results: The levels of proinflammatory cytokines in hippocampus were measured by enzyme-linked immunosorbent assay, and cleaved caspase-3 was detected by Western blot 24 hours after surgery. Neuronal apoptosis was determined by terminal deoxynucleotidyl transferase dUTP nick-end labeling staining 48 hours after surgery. Additional animals were monitored to record survival and body weight changes for 10 days after surgery. Survival animals underwent behavioral tasks 10 days after surgery: open-field, novel object recognition, and continuous multiple-trial step-down inhibitory avoidance task. Ghrelin significantly decreased the levels of proinflammatory cytokines and inhibited the activation of caspase-3 in the hippocampus after cecal ligation and puncture. The density of terminal deoxynucleotidyl transferase dUTP nick-end labeling–positive apoptotic neurons was significantly lowered by ghrelin. In addition, ghrelin improved the survival rates after cecal ligation and puncture. There were no differences in the distance and move time between groups in open-field task. However, the survivors after cecal ligation and puncture were unable to recognize the novel object and required more training trials to reach the acquisition criterion. All these long-term impairments were prevented by ghrelin. Conclusions: Ghrelin inhibited proinflammatory responses, improved the survival rate, and prevented cognitive impairment in septic rats.